Electrical Features of the Diabetic Myocardium. Arrhythmic and Cardiovascular Safety Considerations in Diabetes - Gallego, Mónica; Zayas-Arrabal, Julián; Alquiza, Amaia; Apellaniz, Beatriz; Casis, Oscar (Frontiers in Pharmacology, 2021)
Diabetes is a chronic metabolic disease characterized by hyperglycemia in the absence of treatment. Among the diabetes-associated complications, cardiovascular disease is the major cause of mortality and morbidity in diabetic patients. Diabetes causes a complex myocardial dysfunction, referred as diabetic cardiomyopathy, which even in the absence of other cardiac risk factors results in abnormal diastolic and systolic function. Besides mechanical abnormalities, altered electrical function is another major feature of the diabetic myocardium. Both type 1 and type 2 diabetic patients often show cardiac electrical remodeling, mainly a prolonged ventricular repolarization visible in the electrocardiogram as a lengthening of the QT interval duration. The underlying mechanisms at the cellular level involve alterations on the expression and activity of several cardiac ion channels and their associated regulatory proteins. Consequent changes in sodium, calcium and potassium currents collectively lead to a delay in repolarization that can increase the risk of developing life-threatening ventricular arrhythmias and sudden death. QT duration correlates strongly with the risk of developing torsade de pointes, a form of ventricular tachycardia that can degenerate into ventricular fibrillation. Therefore, QT prolongation is a qualitative marker of proarrhythmic risk, and analysis of ventricular repolarization is therefore required for the approval of new drugs. To that end, the Thorough QT/QTc analysis evaluates QT interval prolongation to assess potential proarrhythmic effects. In addition, since diabetic patients have a higher risk to die from cardiovascular causes than individuals without diabetes, cardiovascular safety of the new antidiabetic drugs must be carefully evaluated in type 2 diabetic patients. These cardiovascular outcome trials reveal that some glucose-lowering drugs actually reduce cardiovascular risk. The mechanism of cardioprotection might involve a reduction of the risk of developing arrhythmia.